Malignant hyperthermia 2020: Guideline from the Association of Anaesthetists. (5th January 2021) - Hopkins, P. M.; Girard, T.; Dalay, S.; Jenkins, B.; Thacker, A.; Patteril, M.; McGrady, E.
Summary: Malignant hyperthermia is defined in the International Classification of Diseases as a progressive life‐threatening hyperthermic reaction occurring during general anaesthesia. Malignant hyperthermia has an underlying genetic basis, and genetically susceptible individuals are at risk of developing malignant hyperthermia if they are exposed to any of the potent inhalational anaesthetics or suxamethonium. It can also be described as a malignant hypermetabolic syndrome. There are no specific clinical features of malignant hyperthermia and the condition may prove fatal unless it is recognised in its early stages and treatment is promptly and aggressively implemented. The Association of Anaesthetists has previously produced crisis management guidelines intended to be displayed in all anaesthetic rooms as an aide memoire should a malignant hyperthermia reaction occur. The last iteration was produced in 2011 and since then there have been some developments requiring an update. In these guidelines we will provide background information that has been used in updating the crisis management recommendations but will also provide more detailed guidance on the clinical diagnosis of malignant hyperthermia. The scope of these guidelines is extended to include practical guidance for anaesthetists dealing with a case of suspected malignant hyperthermia once the acute reaction has been reversed. This includes information on care and monitoring during and after the event; appropriate equipment and resuscitative measures within the operating theatre and ICU; the importance of communication and teamwork; guidance on counselling of the patient and their family; and how to make a referral of the patient for confirmation of the diagnosis. We also review which patients presenting for surgery may be at increased risk of developing malignant hyperthermia under anaesthesia and what precautions should be taken during the peri‐operative management of the patients. 요약: 악성고열증은 국제질병분류(International Classification of Diseases, ICD)에서 전신마취 중에 발생하며 생명을 위협하 는 진행성 고열 반응으로 정의된다. 악성고열증에는 기저 유 전적 베이스가 존재하며, 유전적으로 취약한 개인은 흡입마취 제 또는 석시닐콜린(suxamethonium) 중 하나에 노출되는 경 우 악성고열증의 발생 위험이 있다. 이는 또한 악성 대사과다 증후군으로 설명할 수도 있다. 악성고열증의 특별한 임상적 특 징은 없으며, 이 질환을 초기에 식별하지 못하고 신속하며 적 극적인 치료를 수행하지 않는 경우 치명적일 수 있다. 마취전문 의협회(Association of Anaesthetists)는 모든 수술실에 표기 하여 악성고열증 반응이 발생하는 경우 도움이 될 수 있도록 위기 관리 가이드라인을 작성한 바 있다. 마지막 버전은 2011년 에 작성되었으며, 그 이후로 업데이트가 필요한 일부 개선사항 이 존재한다. 이 가이드라인에서는 위기 관리 권고사항의 업데 이트에 사용된 배경 정보를 제공하는 것뿐만 아니라 악성고열 증의 임상적 진단에 대한 더 자세한 지침을 제공한다. 이 가이 드라인은 급성 반응은 호전되었지만 악성고열증으로 의심되는 증례를 다루는 마취의를 위한 실용적 지침을 포함하도록 확장 되었다. 여기에는 반응 도중 및 반응 후 치료 및 모니터링 정보, 수술실과 중환자실 내의 적절한 장비 및 소생 조치, 의사소통 과 팀워크의 중요성, 환자 및 환자 가족과의 상담 지침, 확진된 환자의 의뢰 방법이 포함된다. 또한, 마취하에 악성고열증 발생 위험이 높은 수술 환자를 식별하고 환자의 수술 전후기 관리 도중 어떤 주의 조치를 취해야 하는지 검토하였다.